2005
DOI: 10.1051/rnd:2005053
|View full text |Cite
|
Sign up to set email alerts
|

The effects of progesterone priming on reproductive performance of GnRH-PGF2α-treated anestrous goats

Abstract: -The objective of this experiment was to determine the effect of a 5-day progesterone priming prior to a GnRH-PGF 2α treatment on reproductive performance of anestrous goats. Thirtysix Mountain Black goats were randomly assigned in a 2 × 2 factorial arrangement and were administered intravaginally on day -12, either with 300 mg progesterone inserts (CGPE and CGP) or with 0 mg progesterone (GPE and GP) for 5 days. On day -6, the goats were injected with 100 µg GnRH, followed 6 days later by 15 mg PGF 2α (day 0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
3
9
1
Order By: Relevance
“…The combination of Levonorgestrel treatment and PGF 2α injection was found to be an efficient method for estrous synchronization in cycling does during the breeding season, and the high estrous response (95.0%) was obtained. However, there was a significant longer time in the onset of estrus (57.8 h), which was similar to or little longer than that reported in other studies (Romano 1996;Husein et al 2005). A longer duration (33.5±9.4 h) was recorded in does subjected to the Levonorgestrel/PGF 2α treatment, which is within the range of that reported by researchers (Romano 1996;Freitas et al 1997).…”
Section: Discussionsupporting
confidence: 88%
“…The combination of Levonorgestrel treatment and PGF 2α injection was found to be an efficient method for estrous synchronization in cycling does during the breeding season, and the high estrous response (95.0%) was obtained. However, there was a significant longer time in the onset of estrus (57.8 h), which was similar to or little longer than that reported in other studies (Romano 1996;Husein et al 2005). A longer duration (33.5±9.4 h) was recorded in does subjected to the Levonorgestrel/PGF 2α treatment, which is within the range of that reported by researchers (Romano 1996;Freitas et al 1997).…”
Section: Discussionsupporting
confidence: 88%
“…Even at latitude 25°N, native breeds are capable to breed in spring (Mellado et al 2006); however, indiscriminate crossbreeding of native goats with dairy breeds originated in the Alps has led to seasonal anoestrous in crossbred goats at this latitude, although this seasonal anestrous is less marked than that observed in temperate zones (males: Todini et al 2007;Zarazaga et al 2009;females: Carcangiu et al 2009;Arrebola et al 2010). Induction of fertile estrus for out of season breeding is important for goat producers in many countries in order to overcome the seasonality of the goat milk supply; thus, a considerable research has been carried out to enable yearround kidding of goats (Husein et al 2005;López-Sebastian et al 2007). Several methods are available to induce off-season cyclicity and estrous synchronization in does.…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal treatment to control ovulation and reproduction is a perquisite for successful breeding and increasing the number of pregnant females (Motlomelo et al. 2002; Husein et al. 2005), resulting in short breeding period and more uniform newborn crop (Husein and Kridli 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2005). Husein et al. (2005) reported that 4‐day progesterone priming ahead of the treatment was essential for the effectiveness of this procedure to maintain follicular response to GnRH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation